Aplikasi Sharing Informasi Masyarakat dan Forum Opini Publik - Andy Yunata; Adi Wibowo; Andreas Handojo (Jurnal Infra, 2016)
Surabaya is the capital city of this province, East Java. Therefore, it is not a surprise when Surabaya has the largest population throughout East Java. With the Surabaya’s characteristic, there are always many urban problems which is occurred everyday. These urban problems become more complex along with the growth of population in Surabaya. With the increasing of the population, then there’ll be more to happen some urban problems such as traffic jam, garbage control, broken infrastructure, lawlessness, renovation of city structure, and many more. Because of that, the effect of various urban issues can be minimalized if there’s some contribution from the citizen theyself. The contribution can be information sharing about urban problem to others so the citizen knows where it occurs, when it happen, and what they should do. Besides that, it would be nice if there’s a facility of public discussion forum so the citizen can directly discuss about problem they are facing right now.After the testing of this application, it has various benefit such as location-based urban problems reporting, public discussion forum, and a social media where citizen meets and greets each other.